Sintesis dan Karakterisasi Katalis Nikel Zeolit Alam Ni/NZA - Bahri, Syaiful; Saputra, Edy; Herman, Syamsu; Muhdarina, Muhdarina (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Research has been conducted to manufacture Ni/NZA for catalytic cracking of empty palm fruit bunches into liquid fuel. The study aims to investigate the impact of metal impregnation and calcination time variations on catalyst crystallinity and morphology. The catalyst is produced in multiple stages, including NZ activation using acid, followed by metal impregnation at 0%, 1%, 3%, and 5% w/w, and calcination at 500oC for 2, 4, and 6 hours, respectively. It is then oxidized at 400oC for 2 hours and reduced at 400oC for 2 hours. The catalyst's crystallinity, morphology, and metal distribution are determined through X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analysis. The catalyst with the best crystallinity and metal distribution is found to have 3% metal loading and a calcination time of 2 hours.